Making simple robots - Ceceri, Kathy (Sebastopol, CA Maker Media, 2015)
"Making Simple Robots is based on one idea: Anybody can build a robot! That includes kids, English majors, school teachers, and grandparents. If you can knit, sew, or fold a flat piece of paper into a box, you can build a no-tech robotic part. If you can use a hot glue gun, you can learn to solder basic electronics into a low-tech robot that reacts to its environment. And if you can figure out how to use the apps on your smart phone, you can learn enough programming to communicate with a simple robot" -- www.oreilly.de
Robots made from interesting materials. Project: Make actuated paper ; Project: Make an inflatable robot -- Robots that get around. Project: Make a compressible tensegrity robot ; Project: Design a wheel-leg hybrid -- Unevolved robots. Project: make a swarm of gliding vibrobots ; Project: Make a souped-up solar BEAM wobblebot -- Robot friends and helpers. Project: Make a chatbot program ; Project: Picture yourself in the uncanny valley -- Fun, artsy robots. Project: Make a littleBits plotter ; Project: Make FiberBot, an e-textile arduino robot -- What I learned writing this book.
"Explore cutting-edge robotics with everyday stuff."--Cover.
Includes index
11 - 17 years
Keywords: Robots -- Design and construction; Handbooks and manuals